USING AN INTEGRATIVE APPROACH IN PROFESSIONAL DIRECTION OF STUDENTS (Conferencea, 2023)
The article examines issues related to the preparation of students for choosing a profession with the help of the integration of "Natural science and its teaching methodology" with natural-scientific sciences on the basis of professional-pedagogical orientation.